IMPLEMENTASI MANAJEMEN HUMAS DALAM MENINGKATKAN POTENSI BAKAT OLIMPIADE SAINS PESERTA DIDIK DI MTSN 1 MADIUN - Al Imaamah Rosyiidatu Uswatun Nisyaa’; Baiq Tuhfatul Unsi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to describe and analyze the implementation of public relations management in enhancing students’ Science Olympiad talent potential at MTsN 1 Madiun. The research focuses on the planning, implementation, evaluation, and strategic efforts carried out by public relations to support academic talent development through partnerships and achievement publication.  This research uses a qualitative approach with a method. Data were collected through in-depth interviews, direct observation, and documentation. The research subjects include the principal, public relations coordinator, Science Olympiad mentor teachers, and high-achieving students. The data analysis technique follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing.  The results show that public relations management at MTsN 1 Madiun is systematically implemented through program planning aligned with the school's vision, cooperation with external institutions, regular evaluation of activities, and potential development strategies such as achievement publication, provision of supporting facilities, and strengthening of partnership networks. The public relations role significantly contributes to fostering a competitive learning environment and supporting students’ success in the Science Olympiad